PRIMARY MYELOFIBROSIS - Muhammad Irhamsyah; Darwati Muhadi; Mansyur Arif (Indonesian Association of Clinical Pathologist and Medical laboratory, 2018)
A 55-year-old male was admitted to hospital with chief complaint of abdominal distention since one year before admission, and it became more prominent than before. The physical examination showed splenomegaly with schuffner line S5, and it was confirmed with ultrasonography. The routine blood test showed a hemoglobin level of 9.2 g/L, leukocyte count of 14.690/µL and thrombocyte count of 115 x 103/µL. From the peripheral blood smear results, the suspected diagnosis of chronic myeloid leukemia with differential diagnosis of a leukemoid reaction was made. However, bone marrow aspiration revealed hypoplastic marrow of primary myelofibrosis. The patients with primary myelofibrosis need early diagnosis and treatment to manage the symptoms of splenomegaly, stop fibrosis process and extramedullary hematopoiesis. Early treatment, in this case, can decrease poor prognosis and mortality rate.